Small screens, big impact: prevalence and associated factors of excessive screen time among 2-5-year-olds in southern Karnataka - Teja, Rangisetti Naga Prudhvi; Sahithya, Vanjavakam; Vardhini N., Bindu; Abdul Khader Moinudeen , Syed (International Journal Of Community Medicine And Public Health, 2025)
Background: Screen time (ST) in early childhood is rapidly increasing, with potential adverse effects on physical, cognitive, and psychosocial development. WHO recommends that children aged 2-5 years should not exceed one hour of screen exposure per day. However, data from rural regions in southern India remain scarce. The study estimated the prevalence of excessive ST among children aged 2-5 years in rural southern Karnataka and examined associated socio-demographic and parental factors. Methods: We conducted a cross-sectional analytical study among 155 parents of children aged 2-5 years in southern Karnataka. Participants were selected through simple random sampling. Data were collected via structured interviews using a pre-tested questionnaire. Excessive ST was defined as >1 hour/day. Descriptive and bivariate analyses were performed using SPSS. Results: Overall, 49.0% (95% CI: 42.5-55.6%) of children exceeded recommended ST limits. Excessive screen use was most prevalent among 3-year-olds (86.7%) and 5-year-olds (50.7%). All households had televisions; 91.6% had at least one smartphone. Daily screen use was reported in over half of the children. Although 93.5% of parents reported regulating ST, only 28.4% were aware of WHO guidelines. Bivariate analysis showed significant associations between excessive ST and the child’s age, parental education, and number of devices at home. Conclusions: Nearly half of rural preschool-aged children in this study exceeded safe ST limits. Despite widespread device access and parental regulation efforts, awareness of guidelines remains low. Targeted education and community-based interventions are essential to mitigate the impact of excessive screen exposure in early childhood.